Status-Seeking in Violent Subcultures and the Double Dividend of Zero-Tolerance - Robert Dur (Tinbergen Institute, 2006)
This paper develops a model in which individuals gain social status among their peers for being 'tough' by committing violent acts. We show that a high penalty for moderately violent acts (zero-tolerance) may yield a double dividend in that it reduces both moderate and extreme violence. The reason is that a high penalty keeps relatively 'gutless' individuals from committing moderately violent acts, which raises the signaling value of that action, and thus makes it more attractive for otherwise extremely violent individuals. Conversely, a high penalty for extremely violent acts may backfire, as it induces relatively 'tough' individuals to commit moderately violent acts and so makes moderate violence more attractive for otherwise nonviolent individuals.
Keywords: K14; K42; 330; status concerns; violence; subcultures; penalties; zero-tolerance; broken windows policing; Gewalt; Sozialer Status; Strafe; Kriminalität; Kriminalitätsökonomik; Rechtsdurchsetzung; Doppelte Dividende; Theorie